Some Results of the Carathedory's Class - Bolcal, Metin; Şen, Arzu; POLATOĞLU, YAŞAR (İstanbul Kültür Üniversitesi Yayınları, 2002)
Bu çalışmada caratheodory sınıfı üzerine bazı sonuçları araştırırız. f(z)=1+p₁z+p₂z²+p₃z³+… fonksiyonu birim dairede analitik olsun ve f(0)=1,Re f(z)≥0, koşullarını gerçeklesin bu durumda f(z) fonksiyonu Caratheodory fonksiyonu olarak adlandırılır.

In this paper we investigate some results on the Caratheodory’s class. Let f(z)=1+p₁z+p₂z²+p₃z³+… be analytic in the unit disc D={z/|z|≤1}, and satisfying the conditions f(0)=1,Re f(z)≥0, then the function f(z) is called the Caratheodory function.
Keywords: positive real part; caratheodory class; coefficient inequality; pozitif reel bölüm; Caratheodory sınıf; katsayı eşitsizliği